THE METHOD OF PRIMARY NECROECTOMY IN THE TREATMENT OF SOFT TISSUE TROPHIC ULCERS IN PATIENTS WITH DIABETES - Tursunov Feruz O’ktam o`g`li; Boboqulova Aziza (TADQIQOTLAR.UZ, 2024)
Introduction. Surgical soft tissue infection in patients with diabetes the clinical picture continues in an atypical manner, if there are no characteristic signs of a purulent process and patients are treated by other specialists. In primary care late diagnosis of pathology due to lack of opportunity to conduct instrumental research methods was Patients with this pathology developed sepsis with organ failure cases are diagnosed.According to WHO, 5-6% of the population of developed countries suffer from diabetes, and the number of these patients is constantly growing and doubles every 10-15 years.